In Silico Study of Active Compounds and Protein Targets of Orthosiphon aristatus as Alternative Therapy for Hypertension: Network Pharmacology and Docking - Adha Dastu Illahi; Nur Hasanah; Gatot Fatwanto Hertono; Arry Yanuar (Eduvest - Journal of Universal Studies, 2024)
Hypertension poses a significant global health burden, prompting exploration into alternative treatments. This study investigates the pharmacological network of Orthosiphon aristatus, aiming to uncover its therapeutic potential for hypertension. We compiled data on Orthosiphon aristatus chemical constituents and predicted potential targets for its key components. Through screening processes utilizing the Gencard database, active compounds and protein targets were identified. We examined protein target similarities between Orthosiphon aristatus and hypertension, constructing a network illustrating the relationships between active compounds and target genes. Additionally, we conducted GO function analysis and KEGG pathway enrichment to elucidate Orthosiphon aristatus role in hypertension. Notably, TP53 exhibited the highest degree of centrality, while Scutellarein and aurantiamide acetate displayed the highest affinities in molecular docking with TP53. These findings offer novel insights into Orthosiphon aristatus' potential as an adjunctive therapy for hypertension and contribute to the advancement of pharmacological interventions in this domain.